(NZW x BXSB)F1 mouse. A new animal model of idiopathic thrombocytopenic purpura (The Rockefeller University Press, 1988)
A decrease in thrombocyte count was observed in (NZW x BXSB)F1 (W/B F1) mice at the age of greater than 5 mo, whereas megakaryocyte counts were found to increase in such mice. FACS analyses revealed the presence of both platelet-associated antibodies (PAA) and circulating antiplatelet antibodies. There is a correlation between the presence of these antibodies and the degree of thrombocytopenia. The transplantation of normal bone marrow cells from BALB/c nu/nu mice to W/B F1 mice was found to have preventative and curative effects on thrombocytopenia; the mice showed normal platelet counts and no evidence of circulating antiplatelet antibodies. These results indicate that thrombocytopenia in W/B F1 mice is due to the presence of antibodies to platelets. We therefore think that W/B F1 mice serve as a useful animal model of idiopathic thrombocytopenic purpura (ITP) not only for elucidating the mechanism of the development of antiplatelet antibodies, but also for characterizing autoantibodies to platelets.